Merger arbitrage : how to profit from event-driven arbitrage - Kirchner, Thomas, 1968- (Wiley finance series., 2016)
"Mitigate risk and increase returns with an alternative hedge fund strategy Merger Arbitrage: How to Profit from Event-Driven Arbitrage, Second Edition is the definitive guide to the ins and outs of the burgeoning merger arbitrage hedge fund strategy, with real-world examples that illustrate how mergers work and how to take advantage of them. Author Thomas Kirchner, founder of the Pennsylvania Avenue Event-Driven Fund, discusses the factors that drove him to invest solely in merger arbitrage and other event-driven strategies, and details the methods used to incorporate merger arbitrage into traditional investment strategies. And while there is always a risk that a deal will fall through, the book explains how minimal such risks really are when the potential upside is factored in. Early chapters of the book focus on the basics of the merger arbitrage strategy, including an examination of mergers and the incorporation of risk into the arbitrage decision. Following chapters detail deal structures, financing, and legal aspects to provide the type of in-depth knowledge required to execute an effective investment strategy. The updated second edition stresses new, increasingly relevant information like: Worldwide legal deal regimes UK takeover code UK takeover code global offspring Regulators around the world The book provides clear, concise guidance on critical considerations including leverage and options, shorting stocks, and legal recourse for inadequate merger consideration, allowing readers to feel confident about trying a new investment strategy. With simple benefits including diversification of risk and return streams, this alternative hedge fund strategy has a place in even the most traditional plan. Merger Arbitrage: How to Profit from Event-Driven Arbitrage, Second Edition provides the information that gives investors an edge in the merger arbitrage arena"--